Pengaruh Penggunaan E-Wallet, Financial Literacy dan Financial Self Efficacy Terhadap Pengelolaan Keuangan Usaha Nail Art di Kota Denpasar - Pradnya Paramita, I Gusti Ayu Mas; Sri Widiantari, Komang (Masyarakat Ekonomi Syariah Bogor, 2025)
The rapid development of financial technology and the increasing use of e-wallets among micro, small, and medium enterprises (MSMEs) have not been fully accompanied by adequate financial management capabilities, particularly among nail art businesses in Denpasar City. Common issues observed include the mixing of personal and business finances, weak transaction recordkeeping, and limited financial knowledge and self-confidence among business owners, despite the use of digital transactions in daily operations. In light of these conditions and the mixed findings of previous studies, this research aims to examine the effects of e-wallet usage, financial literacy, and financial self-efficacy on the financial management of nail art businesses in Denpasar City. This study employs a quantitative approach by distributing questionnaires to 120 respondents who actively use e-wallets as a digital payment method in their business activities. The research instruments were tested for validity and reliability, followed by classical assumption tests and multiple linear regression analysis. The results indicate that e-wallet usage, financial literacy, and financial self-efficacy each have a positive and significant effect on financial management, both individually and simultaneously. Therefore, nail art business owners are encouraged to optimize the use of e-wallets not only as payment tools but also as transaction recording instruments, while continuously improving their financial literacy and financial self-efficacy to better manage cash flow, make sound financial decisions, and mitigate business risks in a more effective and sustainable manner. Future studies are recommended to incorporate additional relevant variables and to apply qualitative or mixed-methods approaches.